Application of Adaptive Fuzzy PID Leveling Controller - Ke Zhang; Jingxian Qin; Jia Sun; Shizhong Chen; Yuhou Wu (Institute of Advanced Engineering and Science, 2013)
Aiming at the levelling precision, speed and stability of suspended access platform, this paper put forward a new adaptive fuzzy PID control levelling algorithm by fuzzy theory. The method is aided design by using the SIMULINK toolbox of MATLAB, and setting the membership function and the fuzzy-PID control rule. The levelling algorithm can real-time adjust the three parameters of PID according to the fuzzy rules due to the current state. It is experimented, which is verified the algorithm have better stability and dynamic performance. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2563